Effect of high-intensity interval training and moderate-intensity continuous training on blood lactate clearance after high-intensity test in adult men - Xie, Han; Mao, Xiaojin; Wang, Zhaohong (Frontiers in Physiology, 2024)
This study compared the effects of High-intensity interval training (HIIT) and moderateintensity continuous training (MICT) on blood lactate clearance. 21 adult males were equally and randomly assigned to the HIIT and MICT groups, and completed 8 weeks of training.Before the training intervention, after four weeks and eight weeks of training, all subjects were tested for blood lactate levels between 0 and 55 minutes after the same high-intensity test. The results show that after 8 weeks, blood lactate levels were significantly lower than pre-tests in both the HIIT and MICT groups at "0-55 minutes" after high-intensity test (p<0.05), and the blood lactate clearance percentage at15-minute and 30-minute in both groups were significantly higher than the pre-tests (P < 0.01). The blood lactate levels in the HIIT group were significantly lower than those in the MICT group at 15 min and 30 min after test (P < 0.05), and the blood lactate clearance percentage at 30 min in the HIIT group was significantly higher than those in the MICT group (P < 0.05). In conclusion, both HIIT and MICT enhance blood lactate clearance in adult males post high-intensity test, with HIIT demonstrating superior effectiveness, making it a viable alternative to MICT.